Highly Efficient Agrobacterium‐Mediated Transformation of Potato (Solanum tuberosum) and Production of Transgenic Microtubers. Issue 1 (2nd April 2018) - Craze, Melanie; Bates, Ruth; Bowden, Sarah; Wallington, Emma J.
Abstract: The following method enables the rapid production of transgenic potato plants and microtubers for gene validation and expression, or promoter studies. The method is highly efficient, with reproducible transformation efficiencies of at least 50% to 60% with potato cv. Desiree, and can produce transgenic microtubers within 6 months of initiation of the experiment. Microtubers are produced in the absence of hormones, giving an in vitro gene testing system broadly analogous to the natural state. © 2018 by John Wiley & Sons, Inc.